ANALYSIS OF PREVALENCE, STRUCTURE AND CLINICAL CHARACTERISTICS OF DENTAL DISEASES IN MILITARY PERSONNEL SERVING IN EXTREME CLIMATIC CONDITIONS. - Jakhonaliyev Begzod Usmonaliyevich; Mirraximova S.Sh (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT This article provides information on the causes, clinical course, and preventive measures for chronic generalized periodontitis in military personnel and in extreme climatic conditions. Nowadays, protecting the health of military personnel and maintaining their high level of combat readiness is one of the main factors in ensuring state security and defense capability, and extreme climatic conditions - very high or low temperatures, drought, wind, sharp changes in humidity, and fluctuations in atmospheric pressure - cause significant physiological and biochemical changes in the human body, including in the structures of the oral cavity.